Effect of the single vacancy in particle pile on heat transfer performance of particle pile. (December 2020) - Zheng, Bin; Tang, Shuai; Sun, Peng; Zhao, Qiang; Liu, Yongqi; Wang, Geoff; Meng, Jian; Shen, Yingkai; Chang, Runze
Abstract: This paper reports the effect of a single vacancy on heat transfer of particle pile. A three-dimensional steady-state heat transfer model of particle pile with a single vacancy was established. The effects on the temperature distribution, heat transfer mode and heat flux characteristics of the particle pile were studied. In the area close to the vacancy, the particle temperature distribution is significantly affected, and the average temperature line is significantly deformed. The heat conduction between particles along the Y-direction is the dominant heat transfer mode around the vacancy. Compared with a particle pile without vacancy, the total heat flux at the hot wall decreases by 0.63% and the apparent thermal resistance of the particle pile increases by 0.71%. The size of the region affected by a vacancy on heat transfer was determined. At the X-direction, the size of the region affected by a vacancy is 1.79 times of particle size. Upstream position of vacancy at the Y-direction, the size of the region is 4.03 times of particle size. Downstream position of vacancy at the Y-direction, the size of the region is 3.81 times of particle size. The research results can be used to improve the thermal resistance network theory.